THE EFFECT of DENTIN PRETREATMENT on THE MICROTENSILE BOND STRENGTH of SELF-ADHESIVE RESIN CEMENTS - Pavan, Sabrina; Santos, Paulo Henrique dos [UNESP]; Berger, Sandrine; Bedran-Russo, Ana Karina B. (Mosby-elsevier, 2010)
Statement of problem. Self-adhesive cements have lower bond strength than conventional resin cements that rely on the application of etch-and-rinse adhesive systems.Purpose. The purpose of this study was to evaluate the effect of tannic and polyacrylic acid on the microtensile bond strength of self-adhesive resin cements to dentin.Material and methods. Eighteen molar crowns were flattened to expose dentin and divided into 3 groups according to the dentin pretreatment: (1) control, without surface treatment; (2) 25% polyacrylic acid solution (Ketac Conditioner); (3) 20% tannic acid. Composite resin (Tescera) blocks were luted to dentin surfaces using 2 self-adhesive resin cements (RelyX Unicem or Maxcem Elite) (n=3). All specimens were stored in distilled water for 24 hours, sectioned into beams (1 mm(2)), and tested to failure using a microtensile method at a crosshead speed of 1 mm/min. The data were statistically analyzed using 2-way ANOVA and Fisher's PLSD tests (alpha=.05).Results. The polyacrylic acid significantly improved the microtensile bond strength of RelyX Unicem (14.92 +/- 4.94 MPa) when compared to the control group (8.35 +/- 1.99 MPa) and tannic acid treatment (8.38 +/- 2.67 MPa) (P<.001). Dentin surface treatment did not affect the microtensile bond strength of Maxcem Elite cemented groups (control, 8.45 +/- 3.21 MPa; polyacrylic acid, 9.53 +/- 9.95 MPa; tannic acid, 6.89 +/- 4.45 MPa).Conclusions. Dentin pretreatment with polyacrylic acid improved the microtensile bond strength of RelyX Unicem. (J Prosthet Dent 2010; 104:258-264)